PENYUSUNAN DOKUMEN SOP PROSES PRODUKSI SUSU PASTEURISASI BERBASIS TEKNOLOGI PEF DI CV. MILKINESIA NUSANTARA - Della Angelina; Teti Estiasih; Anugerah Dany Priyanto; Angky Wahyu Putranto; Widyasari . (UPN Veteran Jawa Timur, 2023)
CV. Milkinesia Nusantara is micro scale fresh milk processing business in Ponorogo Regency. CV. Milkinesia Nusantara will develop pasteurized milk production by Pulsed Electric Field technology and build new production place. Therefore, document that must be prepared is standard operating procedure document of production to support production activities. The data collection method for preparing SOP documents in this final project is qualitative descriptive methods. In addition, the TPC of milk samples are also tested in the laboratory as data to verify the adequacy of pasteurization. The results obtained are draft of production SOP document which is consist of introduction, overview of pasteurized milk processing, and the stages of each process. The combination of pre-heating (70oC; 20 minutes) and Pulsed Electric Field (18 kV; 4 minutes; frequency 8.197 kHz; pulse width 66 μs) in pure cow’s milk as data to verify the adequacy of pasteurization is able to reduce the total number of microbes by 99% (2 log cycles) which data is in accordance to the SNI for pasteurized milk, but the microbial reduction isn’t in accordance with the minimum limit on the 5D concept. In general, the evaluation of SOP document draft in CV. Milkinesia Nusantara were responses, inputs, and suggestions related to draft of SOP.